2015
DOI: 10.1179/1743676115y.0000000059
|View full text |Cite
|
Sign up to set email alerts
|

Spark plasma sintered superplastic deformed transparent ultrafine hydroxyapatite nanoceramics

Abstract: Hydroxyapatites (HAs) are used as bioceramics for artificial bone substitutes because of their good biocompatibility. In this study, highly transparent ultrafine HA ceramics with a mean grain size of 170 nm were synthesised by spark plasma sintering at 900-10008C and 80 MPa. Phase analysis revealed the presence of a pure HA phase even after sintering at 10008C. The sintered body was almost fully dense (.99%). The total forward transmission was .70% at 400 nm, and it approached the theoretical value of 89% in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, the SPS samples had an almost uniform grain size, whereas the flash-sintered samples showed wide variations in grain size. 17 Although the hardness of the flash-sintered samples was not measured, it may be expected to be higher than the SPS and conventionally sintered samples because the hardness is inversely proportional to the grain size (H ∝ G −1/2 , where H is the hardness and G is the grain size). 18 These results showed that a proper combination of electrical power dissipation and temperature densified HA within very short sintering time.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the SPS samples had an almost uniform grain size, whereas the flash-sintered samples showed wide variations in grain size. 17 Although the hardness of the flash-sintered samples was not measured, it may be expected to be higher than the SPS and conventionally sintered samples because the hardness is inversely proportional to the grain size (H ∝ G −1/2 , where H is the hardness and G is the grain size). 18 These results showed that a proper combination of electrical power dissipation and temperature densified HA within very short sintering time.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases, a transparency is convenient to provide some essential advantages (e.g., to enable direct viewing of living cells, their attachment, spreading, proliferation, and osteogenic differentiation cascade in a transmitted light). Thus, transparent CaPO 4 bioceramics (Figure 6) [419] have been prepared and investigated [69,87,185,187,[310][311][312][313][314][315][419][420][421][422][423][424][425][426][427]. They can exhibit an optical transmittance of ~66% at a wavelength of 645 nm [425].…”
Section: Possible Transparencymentioning
confidence: 99%
“…While biomedical applications do not require high temperatures, the ability to superplastically deform provides another processing route for final shaping of ceramic components. Han et al synthesised highly transparent ultrafine HA ceramics with a mean grain size of 170 nm by SPS at 900–1000°C and 80 MPa [105]. The sintered body was almost fully densified (>99%).…”
Section: Transparent Hamentioning
confidence: 99%